Four-dimensional echocardiographic quantification of left atrial function in metabolic syndrome across different diastolic function states - Haihui Liang; Xuebing Zhao; Chengwei Xiao; Lijuan Sun; Fang Zhang (BMC Cardiovascular Disorders)
Abstract Background Metabolic syndrome (MS), characterized by insulin resistance and systemic inflammation, is closely associated with increased cardiovascular morbidity. Although left atrial (LA) dysfunction is now recognized as an early indicator of cardiometabolic impairment, the progression of LA phasic functional changes across stages of diastolic dysfunction in MS remains poorly quantified. Emerging four-dimensional automatic LA quantification (4D-LAQ) enables more precise assessment of metabolism-induced cardiac remodeling. Purpose To assess alterations in LA function among MS patients with different stages of diastolic dysfunction using 4D-LAQ. Methods A total of 72 patients with MS and 34 healthy volunteers were included. MS patients were divided into three groups based on their diastolic function status. General clinical indicators and standard echocardiographic measurements were obtained. 4D-LAQ was used to quantify LA volume and strain parameters, which were then compared among the groups. Results LA volume parameters were significantly increased in all three MS groups compared to the control group, while LA strain parameters were reduced (p < 0.05). In the group with diastolic dysfunction, LA volume was further increased, and LA strain parameters as well as the LA emptying fraction (LAEF) were significantly lower than in the other groups (p < 0.05). Conclusion 4D-LAQ allows reliable assessment of LA volume, strain, and functional changes in MS patients, particularly during left ventricular (LV) diastolic dysfunction. This approach may contribute to improved diagnosis, treatment planning, and clinical evaluation in patients with MS.